1999
DOI: 10.4049/jimmunol.162.8.4983
|View full text |Cite
|
Sign up to set email alerts
|

CTLA4 Signals Are Required to Optimally Induce Allograft Tolerance with Combined Donor-Specific Transfusion and Anti-CD154 Monoclonal Antibody Treatment

Abstract: Sensitization to donor Ags is an enormous problem in clinical transplantation. In an islet allograft model, presensitization of recipients through donor-specific transfusion (DST) 4 wk before transplantation results in accelerated rejection. We demonstrate that combined DST with anti-CD154 (CD40L) therapy not only prevents the deleterious presensitization produced by pretransplant DST in the islet allograft model, it also induces broad alloantigen-specific tolerance and permits subsequent engraftment of donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…CTLA4, a member of the CD28 family, competes with CD28 binding to the same ligands (B7.1 and B7.2; B7 hereinafter) and delivers an inhibitory signal to T-cell activation. 70 Inhibition of this pathway has been reported to attenuate acute cardiac rejection and prolonged graft survival, 32-35 but not induce stable tolerance, 71 as CAV still developed in this model. 36 Additionally, targeted therapies directed at CTLA4 are associated with significant morbidity and side effects.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…CTLA4, a member of the CD28 family, competes with CD28 binding to the same ligands (B7.1 and B7.2; B7 hereinafter) and delivers an inhibitory signal to T-cell activation. 70 Inhibition of this pathway has been reported to attenuate acute cardiac rejection and prolonged graft survival, 32-35 but not induce stable tolerance, 71 as CAV still developed in this model. 36 Additionally, targeted therapies directed at CTLA4 are associated with significant morbidity and side effects.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have demonstrated that treatment with CTLA4-Ig at the time of transplant significantly prolongs heart allograft survival when compared with untreated mice (MST: 60 versus 9 d for treated and untreated recipients, respectively; P < 0.001). 31 Although previous studies have shown that inhibition of CTLA pathway mitigated acute cardiac rejection and prolonged graft survival in murine models, 32-35 CAV still occurred in the recipient animals. 36 To determine whether DT-061 could provide additional benefit in the presence of CTLA4-Ig treatment, we first examined whether DT-061 had a synergistic effect with CTLA4-Ig on transplanted heart rejection tolerance (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Tregs from mIL-2–treated mice had increased production of IL-10 ( Figure 7H ) and LAP, a TGF-β–associated protein ( Figure 7I ). Since CTLA-4 + Tregs are essential for allogenic tolerance ( 48 , 49 ) and immune modulation ( 50 ), we investigated the role of CTLA-4 in the mIL-2–induced prolongation of transplant survival. We used a combination of 2 non-Treg-depleting anti–CTLA-4 monoclonal antibodies (clone UC10-4F10-11 ( 49 , 51 , 52 ) and 9H10 ( 53 )) in OVA skin graft recipient mice treated with mIL-2 or control ( Figure 7J ).…”
Section: Resultsmentioning
confidence: 99%
“…The suppressive function of Tregs involves myriad mechanisms, including the secretion of immunomodulatory cytokines (e.g., IL-10), downmodulation of DCs, and coinhibitory receptor signaling through CTLA-4 with induction of indoleamine 2, 3-dioxygenase (IDO) ( 13 ). In transplantation, the expression of coinhibitory receptors and cytokines such as IL-10 has been demonstrated to be essential for Tregs’ ability to abrogate alloimmune responses ( 48 , 51 , 83 85 ). Equally important to increasing the number of Tregs was ensuring that their function was preserved or enhanced upon mIL-2.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative protocols use the infusion of “live” donor cells in combination with costimulation blockade, namely anti-CD40L, at the time of transplantation. This protocol has been repeatedly shown to produce a long-term and robust form of tolerance to murine islet ( 7 , 8 ), skin ( 9 ), and cardiac allografts ( 7 , 10 , 11 ), as well as nonhuman primate models of skin ( 12 ) and kidney ( 13 ) transplantation. Yet, the molecular response to the aforementioned donor cell alloinfusion remains poorly understood in contexts of both tolerance induction and basic cellular physiology of immune cells.…”
Section: Introductionmentioning
confidence: 99%